2018
DOI: 10.1177/1069072718788787
|View full text |Cite
|
Sign up to set email alerts
|

A Rasch Analysis of the Tims, Bakker, and Derks (2012) Job Crafting Scale

Abstract: A Rasch validation was performed on the Tims, Bakker, and Derks’s Job Crafting Scale (JCS) in the South African working context. The JCS, which has been linked to employee well-being and career-related outcomes, continues to be the most widely used measure of job crafting behavior. Data obtained from the JCS generally showed good fit to the Rasch model. Four items were flagged during the analysis for displaying misfit (1 item) or differential item functioning (3 items), warranting further research attention. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…The work-home resources model proposes that personal affective resources are the bridge between the work domain and the home domain (ten Brummelhuis and Bakker, 2012). Abundant research findings have suggested that job crafting can generate positive emotions (Slemp and Vella-Brodrick, 2014), enhance job satisfaction (Kim et al, 2018), and increase employees' wellbeing (Peral and Geldenhuys, 2019). More specifically, task crafting provides working mothers with a greater sense of accomplishment, relational crafting allows them to be more influential, and cognitive crafting gives them a greater sense of meaning.…”
Section: Mothers' Job Craftingmentioning
confidence: 99%
“…The work-home resources model proposes that personal affective resources are the bridge between the work domain and the home domain (ten Brummelhuis and Bakker, 2012). Abundant research findings have suggested that job crafting can generate positive emotions (Slemp and Vella-Brodrick, 2014), enhance job satisfaction (Kim et al, 2018), and increase employees' wellbeing (Peral and Geldenhuys, 2019). More specifically, task crafting provides working mothers with a greater sense of accomplishment, relational crafting allows them to be more influential, and cognitive crafting gives them a greater sense of meaning.…”
Section: Mothers' Job Craftingmentioning
confidence: 99%